The economics of tax policy - Auerbach, Alan J.; Smetters, Kent A. (Kent Andrew) (Oxford University Press, 2017)
The debates about the what, who, and how of tax policy are at the core of politics, policy, and economics. 'The Economics of Tax Policy' provides an accessible overview of recent research in the economics of taxation.